The Role of Leadership Style of Head of Ward, Electronic Documenting, and Nurses' Performance in Service Innovation in Meuraxa Hospital - Basyah, Halimatussakdiah; Lubis, Abdul Rahman; Yunus, Mukhlis; Darsono, Nurdasila (The South East Asian Journal of Management, 2018)
Between 74 and 85% of health documentation in advanced countries is conducted by internet, and 80% of customers use those data to seek information related to health service. The research reported in the present paper is aimed at finding out the influence of leadership style of head of ward, electronic documenting, and nurse performance on service innovation in Meuraxa Hospital in 2017. This study is a cross-sectional; survey of 100 nurses at Meuraxa Hospital who were doing electronic documentation. Structural equation modelling (SEM) showed that the respondents’ perception of the leadership style of the head of the ward is agree and strongly agree where the average is 4.22. The respondents’ perception on the use of electronic documentation is agree and strongly agree where the average index is 4.20; and most of respondents’ perception on the innovation on nursing service is agree and strongly agree where the average index is 4.23. All the indices are in the cutoff value range. The result of this study shows a positive correlation: there is an influence of head of ward leadership style on the performance of nurse; the electronic documentation has an effect on the performance of the nurses; the performance of nurses has an effect on the innovation of nursing service; The leadership style of head of ward affects the innovation of nursing service. the electronic documentation can influence the improvement of nursing service innovation. There is an indirect influence of head of ward leadership style, electronic documentation, nurse perfomance on nursing on service innovation through nurse performance. The alternative hypotheses are accepted and fit model test is good. It is hoped that all head of wards and nurses can improve their service by doing documentation comprehensively.